Artificial Immune System with Negative Selection Applied to Facial Biometry Based on Binary Pattern Characteristics - Silva, Jadiel C. [UNESP]; Lima, Fernando P. A. [UNESP]; Lotufo, Anna Diva P. [UNESP]; Batista, Jorge M.M.C.P. (World Scientific Publishing, 2019)
This work aims to explore resources and alternatives for 3D facial biometry using Binary Patterns. A 3D facial geometry image is converted into two 2D representations, appointed as descriptors: A Depth Map and an Azimuthal Projection Distance Image. The first is known as traditional facial geometry, and the second is normal facial geometry that is able to capture the information of different geometries. The characteristics of Local Binary Patterns, Local Phase Quantisers and Gabor Binary Patterns were used with the Depth Map and Azimuthal Projection Distance Image to produce six new facial descriptors: 3D Local Binary Patterns, Local Azimuthal Binary Patterns, Local Depth Phase Quantisers, Local Azimuthal Phase Patterns, and Local Depth Gabor Binary Pattern Magnitudes and Phases. Then, this work uses the immune concept to propose a new approach to realize facial biometry, where the eight new facial descriptors were applied to an Artificial Intelligence algorithm named Artificial Immune Systems of Negative Selection. The analysis of the results shows the efficiency, robustness, precision and reliability of this approach, encouraging further research in this area.
Keywords: artificial immune system of negative selection; artificial intelligence; binary pattern; detection and classification; facial geometry; Identity recognition; intelligent systems